Divergence in technical efficiency of electric utilities: Evidence from the SAPP - Jaunky, Vishal (Elsevier Science, 2013)
This paper investigates the convergence pattern of technical efficiency of the South Africa Power Pool (SAPP) utilities over the period April 2003-March 2010 by means of parametric and non-parametric techniques. Technical efficiency scores are computed via both stochastic frontier analysis and data envelopment analysis. Mixed results are obtained from the neoclassical convergence approaches. In addition, distribution dynamics methods reveal some evidence of club-formation and this result is supported with the occurrence of ?-divergence. Taken as a whole, technical efficiency is found to diverge among the utilities operating in the power pool. © 2013 Elsevier Ltd.